Effect of the Premature Infant Oral Motor Intervention on Sucking Capacity in Preterm Infants in Turkey: A Randomized Controlled Trial. (17th December 2022) - Guler, Selver; Cigdem, Zerrin; Lessen Knoll, Brenda S.; Ortabag, Tulay; Yakut, Yavuz
Abstract : Background: Preterm infants have oral feeding difficulty that often delays discharge, indicating a need for evidence-based interventions for oral–motor development. Purpose: To test the Premature Infant Oral Motor Intervention (PIOMI) on the development of oral–motor function, feeding, and anthropometric outcomes using sucking manometry. Methods: A single-blind randomized experimental design was conducted with a sample of 60 preterm infants from 2 neonatal intensive care units between May 2019 and March 2020. The experimental group received PIOMI for 5 min/d for 14 consecutive days. Sucking capacity, anthropometrics (weight and head circumference), bottle feeding, breast/chest feeding initiation, and length of hospital stay were measured. The Yakut Sucking Manometer (PCT/TR2019/050678) was developed specifically for this study and tested for the first time. Results: The experimental group had a statistically significant percent increase over controls in sucking power (69%), continuous sucking before releasing the bottle (16%), sucking time (13%), and sucking amount (12%) with partial η 2 values of interaction between the groups of 0.692, 0.164, 0.136, and 0.121, respectively. The experimental group had a higher increase in weight (89%) and head circumference (81%) over controls ( F = 485.130, P < .001; F = 254.754, P < .001, respectively). The experimental group transitioned to oral feeding 9.9 days earlier than controls ( t = −2.822; P = .007), started breast/chest feeding 10.8 days earlier ( t = 3.016; P = .004), and were discharged 3.0 days earlier. Implications for Research/Practice: The PIOMI had a significant positive effect on anthropometrics, sucking capacity, readiness to initiate bottle and breast/chest feeding, and a 3-day reduction in length of hospital stay.